Factors affecting the usage of Library e-services in the aftermath of COVID-19 Pandemic / Nurfatihah S Baharuddin and Mohamad Rahimi Mohamad Rosman - S Baharuddin, Nurfatihah; Mohamad Rosman, Mohamad Rahimi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
The emergence of pandemic disease caused havoc throughout the countries. A disease like no other before, Novel Coronavirus 2019 (COVID-19) has affected most of the countries in the world, regardless of the nation's reputation. The danger of deadly infection has caused many governments to lockdown their countries, limiting access and freedom of movement. Malaysia, as well, is affected by this deadly predator. The government of Malaysia has announced the movement control order (MCO) to break the chain of spread. The order caused many service providers to reshape and transforms their service delivery. Libraries are one of the service providers that are affected by this movement control order. Thus, libraries have shifted their operation towards the e-services, in which users can access the library from the comfort of their own house. However, little is known regarding the factors affecting the usage of library e-services in the context of a pandemic. Thus, this study aims to investigate the factors affecting the usage of library e-services in the aftermath of COVID-19 pandemic. A quantitative study was conducted; a total of 192 responses were recorded and analyzed. Findings show that six out of seven hypotheses were accepted. The result shows that information quality and responsiveness are significant predictors of the usage of library e-services, while perceived barriers did not have a significant relationship with the usage of e-services.